Rifampin, ampicillin, streptomycin, and their combinations in the treatment of enterococcal pyelonephritis in rats. - Oill, P A (1981)
The activities of ampicillin, rifampin, streptomycin, and their combinations were evaluated in vitro against Streptococcus faecalis strain GK and in vivo in rats with an established pyelonephritis resulting from challenge with this same enterococcus. In vitro synergy was demonstrated between all combinations. Comparison of the log colony-forming units of S. faecalis recovered per gram of kidney tissue showed that all treated groups had significant lower numbers than controls (P less than 0.001). Ampicillin plus streptomycin or ampicillin alone was superior to rifampin alone or rifampin plus streptomycin at each interval (P less than 0.001). There was no significant difference between ampicillin and rifampin plus ampicillin. The disparity between in vitro and in vivo results again raises some doubts as to the relevance of in vitro observations to clinical outcome.